2016
DOI: 10.1186/s12863-015-0309-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of pig birth weight variability

Abstract: BackgroundPiglet birth weight variability, a trait also known as the within-litter homogeneity of birth weight, reflects the sow’s prolificacy, because it is positively genetically correlated with preweaning mortality but negatively correlated with the mean growth of piglets during sucking. In addition, the maternal additive genetic variance and heritability has been found exist for this trait, thus, reduction in the variability of piglet birth weight to improve the sow prolificacy is possible by selective bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 66 publications
0
17
0
5
Order By: Relevance
“…Estimates of residual variance per animal were used as response variables by Mulder, Crump, et al (2013) and deregressed EBVs (dEBVs) were used by Sell-Kubiak, Duijvesteijn, et al (2015) to identify genomic regions associated with variability of somatic cell score (SCS) in dairy cattle and litter size in pigs, respectively. Wang, Liu, Deng, Yu, and Li (2016), Wang et al (2017) and Wolc et al (2012) used phenotypic standard deviation and CV of BW in pigs and egg weight in chickens, respectively, as response variables in traditional linear models. This range of response variables is partly due to problems in getting a proper measure of residual variance per genotype (see also the discussion on statistical models to estimate genetic variation in residual variance), but also partly because genotypic and phenotypic information may be available on different animals.…”
Section: Associationsmentioning
confidence: 99%
“…Estimates of residual variance per animal were used as response variables by Mulder, Crump, et al (2013) and deregressed EBVs (dEBVs) were used by Sell-Kubiak, Duijvesteijn, et al (2015) to identify genomic regions associated with variability of somatic cell score (SCS) in dairy cattle and litter size in pigs, respectively. Wang, Liu, Deng, Yu, and Li (2016), Wang et al (2017) and Wolc et al (2012) used phenotypic standard deviation and CV of BW in pigs and egg weight in chickens, respectively, as response variables in traditional linear models. This range of response variables is partly due to problems in getting a proper measure of residual variance per genotype (see also the discussion on statistical models to estimate genetic variation in residual variance), but also partly because genotypic and phenotypic information may be available on different animals.…”
Section: Associationsmentioning
confidence: 99%
“…Additionally, there a basic science related vibe in this study as it may provide some mechanistic explanation to relative success of intrauterine competition of the fetuses in species with larger size of litter [5].…”
Section: Bmc Geneticsmentioning
confidence: 97%
“…With the widespread use of customized single nucleotide polymorphism (SNP) arrays, an increasing number of potential markers have been identified by genome-wide association study (GWAS). Wang X. et al (2016) found over two hundred SNPs associated with birth weight by using first parity sows whose offspring had extreme birth weights; Zhang et al (2018) identified 17 genomic regions associated with birth weight; Wang et al (2017) found 12 SNPs that were significantly associated with piglet uniformity; and 27 differentially selected regions associated with the birth weight of piglets were detected by Zhang et al (2014). However, a birth weight GWAS of Large white pigs by Wang et al (2018) was unable to determine any significant loci.…”
Section: Introductionmentioning
confidence: 99%